Cereals as sources of lysine in the reformulation of meat products. Evaluation using a biosensor - Erika Alvarez Cañarte; Guilber Vergara Velez; Frank Guillermo Intriago Flor; Efrain Pérez Vega; Miguel Andrès Falconi Vèlez; Delia Noriega Verdugo; Génesis Pamela García García; Livis Sharith Díaz Alarcón; Andrés Miguel Anchundia Loor; Carlos Jadán-Piedra; Felipe Jadán Piedra (Biosensors and Bioelectronics: X)
The energy and protein requirements of the population must be met, and the use of new analytical methods for rapid, low-cost detection of essential elements like lysine in reformulated foods is crucial. In this context, conditions were evaluated to develop a biosensor with lysine alpha oxidase (LOx), which showed high affinity for lysine with a KM of 0.32 mM. Different concentrations of cereals and legumes (70-30; 55-45; 85-15; quinoa-Lablab Purpureus; pole beans-Lablab Purpureus; and rye-Lablab Purpureus) were incorporated into meat sausages to enrich lysine, achieving a significant increase in lysine concentration (up to 75%) when 15% quinoa was substituted. The potentiometric signal, related to oxygen consumption during lysine oxidation, was detected at 15 s using a voltage of −600 mV. The biosensor, coupled with the immobilized enzyme, allowed the use of low volumes. A positive relationship was found between oxygen consumption (mg O2/L∗s-1) and lysine concentration in the range of 0.01–0.2 mM, with an R2 of 0.9964. The immobilized enzyme-based sensor demonstrated good sensitivity (0.01 mM) and the membrane could be reused up to 18 times, maintaining 92% of its initial activity after 70 days. The biosensor method showed minimal residue formation and had a strong correlation with high-performance liquid chromatography (HPLC) results, validating its accuracy.